2010
DOI: 10.3727/105221610x12717040569866
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Shh and BMP Signaling in the Potential Conversion of Human Adipose Tissue Stem Cells Into Neuron-Like Cells In Vitro

Abstract: The nervous system (NS) has a limited self-repair capability and adult neurogenesis is limited to certain regions of the brain. This generates a great interest in using stem cells to repair the NS. Previous reports have shown the differentiation of adipose tissue-derived mesenchymal stem cells (ASCs) in neuron-like cells when cultures are enriched with growth factors participating in embryonic and adult neurogenesis. Therefore, it could be thought that there exists a functional parallelism between neurogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 78 publications
1
22
1
Order By: Relevance
“…They have the capacity to differentiate in vitro into mesodermal and nonmesodermal lineages. One of the cell type obtained in vitro was neuron-like cells (Safford et al 2002;Ashjian et al 2003;Dhar et al 2007;Anghileri et al 2008;Cardozo et al 2010;Jang et al 2010); and in vivo may contribute to functional benefits in a wide range of neurological insults (Kang et al 2003;Kim et al 2007;Kulikov et al 2008;Wei et al 2009;Chi et al 2010). This transdifferentiation to nonmesodermal lineages of hASCs is supported by the expression of genes across the three germ layers (Boquest et al 2005;Katz et al 2005;Peroni et al 2008).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…They have the capacity to differentiate in vitro into mesodermal and nonmesodermal lineages. One of the cell type obtained in vitro was neuron-like cells (Safford et al 2002;Ashjian et al 2003;Dhar et al 2007;Anghileri et al 2008;Cardozo et al 2010;Jang et al 2010); and in vivo may contribute to functional benefits in a wide range of neurological insults (Kang et al 2003;Kim et al 2007;Kulikov et al 2008;Wei et al 2009;Chi et al 2010). This transdifferentiation to nonmesodermal lineages of hASCs is supported by the expression of genes across the three germ layers (Boquest et al 2005;Katz et al 2005;Peroni et al 2008).…”
Section: Introductionmentioning
confidence: 95%
“…The most common techniques used for differentiating ASCs into the neural lineage involve treatment of the cells with retinoic acid (RA), butylated hidroxyanisole (BHA), different growth factors, inhibition of BMP signaling and growth at low density (Safford et al 2002;Zuk et al 2002;Ashjian et al 2003;McCaffery et al 2003;Dhar et al 2007;Anghileri et al 2008;Cardozo et al 2010;Jang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…ADSCs exhibit the mesenchymal stem cell (MSC) phenotype (Bourin et al, 2013;Zimmerlin et al, 2013), as evidenced by the expression of MSC markers such as CD44, CD73, CD90 and CD105. They can successfully differentiate into adipocytes, osteoblasts and chondrocytes, and have been trans-differentiated into other mesoderm cell types such as insulin producing cells (Karaoz et al, 2013;Moshtagh et al, 2013), hepatocytes (Aurich et al, 2009;Okura et al, 2010) and neuronal-like cells (Cardozo et al, 2010;Rezanejad et al, 2014). ADSC transplantation ameliorated some diseases such as cranio-maxillofacial hard-tissue defects (Sandor et al, 2014), non-revascularizable critical limb ischemia (Bura et al, 2014), acute myocardial infarction and heart failure (Panfilov et al, 2013), complex perianal fistula in Crohn's disease (de la Portilla et al, 2013;Garcia-Olmo et al, 2009), and chronic myocardial ischemia (Qayyum et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relatively small number of ADSC to explain the overall functional recovery in the reported studies, their presence signifies "transdifferentitation" as a possible mechanism underlying the positive therapeutic impact (Gutierrez-Fernandez et al 2013a). Indeed, the capacity of neural differentiation for ADSC has been extensively investigated (Cardozo et al 2010;Kompisch et al 2010;Liao et al 2010;Qian et al 2010;Abdanipour et al 2011;Yu et al 2011;Ahmadi et al 2012). It has also been reported that, compared with bone marrow-derived mesenchymal stem cells, ADSC have superior neurogenic potential (Kang et al 2004).…”
Section: Transdifferentiationmentioning
confidence: 99%
“…A study investigating the fate of human ADSC from different human donors after being subcutaneously injected into immunodeficient SCID mice showed that the cells survived for at least 17 months with subsequent differentiation into fibroblasts of the subdermic connective tissue and into mature adipocytes of fat tissue, exclusively at the site of injection without evidence of migration or fusion with host cells (Lopez-Iglesias et al 2011), underscoring the safety of ADSC transplantation. Moreover, the use of terminally differentiated ADSC may be a possible option for minimizing the risk especially when the protocols for in vitro transdifferentiation of ADSC into neuronal lineage have been well-documented (Cardozo et al 2010;Kompisch et al 2010;Liao et al 2010;Qian et al 2010;Abdanipour et al 2011;Yu et al 2011;Ahmadi et al 2012). Indeed, the use of induced ADSC has been endorsed as a promising therapeutic option in stroke treatment (Yang et al 2011;Shen et al 2013).…”
Section: Adsc Against Stroke: Concerns and Speculationsmentioning
confidence: 99%